Implementation of Government Relation at PT Orbit Future Academy - Syah, Mahaditha Azzahra; Sagita, Novi Indrawati; Taryana, Agus (Jurnal Governansi, 2026)
In the era of digital transformation and the Fourth Industrial Revolution, the role of the private sector in supporting national development has become increasingly significant, particularly through strategic synergy with the government. This study in PT Orbit Future Academy (OFA), a company engaged in technology-based education and training, to establish effective relationships with government institutions in order to strengthen its position within the national education ecosystem. This research is a descriptive qualitative approach grounded in the theoretical framework of government public relations, specifically based on the principles of government public relations as outlined in Minister of Administrative and Bureaucratic Reform Regulation No. 30 of 2011 concerning General Guidelines for Public Relations Governance in Government Institutions. The results show that OFA actively implements Government Relations strategies through partnerships with the Ministry of Manpower, the National Professional Certification Agency (BNSP), the Higher Education Service Institution (LLDIKTI), and regional education offices. Programs such as AWS re/Start, Orbit Skill Center, and Sekolah@2024 demonstrate OFA’s tangible contribution to government policy in improving human resource competencies. However, the company still faces challenges, including complex bureaucracy, regulatory misalignment, and the absence of a dedicated Government Relations Officer. This study recommends that OFA develop a more structured Government Relations system, enhance human resource capacity in the field, and expand communication networks with both central and regional government institutions to strengthen cross-sector collaboration in advancing technology-based education and training.